The UFO People: A Curious Culture by M. J. Banias - Bullard, Eddie (Journal of Scientific Exploration, 2019)
The UFO People has the rare distinction of being a UFO book that is not about UFOs. Author MJ Banias relegates the flying objects to the background along with usual questions of whether they are, what they are, and where they come from. The title signals where his interests lie, and he joins a growing band of scholars with humanistic approaches to the UFO subject. Jodi Dean, Brenda Denzler, Jeffrey Kripal, D. W. Pasulka, and the contributors to Robbie Graham’s anthology, UFOs: Reframing the Debate, have broadened the inquiry past radar analysis or psychometrics to philosophical, cultural, and religious issues. It is in this spirit that Banias looks at the people attracted to UFOs and the culture they form. Banias declares from the outset that he does not know what UFOs are. He has earned his credentials, having investigated for MUFON, worked with noted ufologists, interviewed both ordinary experiencers and ufological celebrities. He acknowledges that UFOs are real enough for people to see and be affected, stricken, fascinated by them, to have lives and outlooks altered. The experiences of thousands of people are undeniable, but the nature of those sights in the sky remains open to question and the evidence ambiguous. Anyone, proponent or skeptic, who claims to know all the answers is guilty of overreach. If uncertainty surrounds the objects, we can learn much about the collective relationship of people with the subject and the rest of society. Most people have heard of UFOs and many believe they are real, making UFOs perhaps the most popular paranormal belief today. Here’s a story worth a closer look. It leads into the intellectual living rooms of UFO followers, into a gap between the life of going to work and mowing the lawn, and a life of experiences that should not happen and possibilities that should not be thought, much less believed. This gap is a haunted place at the cultural fringe where heresies thrive and subvert established norms, where ordinary people turn against the ordinary and become the Other, in a sense alien themselves.